Application of GIS techniques to analysis of spatial distribution patterns of loom-weights, spindle-whorls and tokens at Pistiros, ancient Thrace, within a domestic/urban context - Malgorzata Grzybalska (Virtual Archaeology Review)
A long-term systematic international excavation project has attested the existence of a wide range of past human activities in the emporion Pistiros. An assemblage of artefacts indicating the conduct of different economic activities on the site includes an interesting collection of loom-weights, spindle-whorls and tokens. The purpose of this paper is to look at archaeological material from social, cultural and economic perspectives to understood fully the everyday life of the inhabitants of this trading centre from the Classical to early Hellenistic period (second half of the fifth to second centuries B.C.). To achieve this goal spatial mapping techniques (GIS) were applied to analyse distribution patterns of objects associated with the textile industry within a domestic context.